Evaluation of the Service Quality of the Jaticempaka Village Website, Bekasi City, Using the PIECES Method - Harna Govin Pratama; Yopi Handrianto (SAN Scientific, 2023)
Government agencies have widely used advances in information technology in the modern era to improve public services. Websites have become one of the popular media for accessing information. Jati Cempaka Village, Bekasi City, is one of the institutions that has implemented websites to provide, convey, and publish public information in the context of good governance. This research aims to understand, analyze, and improve the quality of local government website services to support transparency, community participation, and more efficient and effective services. Provide recommendations for appropriate improvements or enhancements to improve the service quality of the Jati Cempaka Village website so that it can provide better benefits to the community and users. The research method used is the PIECES method, which can be used to review and evaluate information systems in an organization, company, or institution. This method analyzes several aspects: performance, information, economy, security, efficiency, and service. In addition, the PIECES method helps analyze the quality of website services with a structured approach and can provide concrete guidance for necessary improvements. User satisfaction based on the analysis of website quality using the PIECES method, it can be concluded that the quality of website-based information services provided by Jati Cempaka Village, Bekasi City, as a community media is considered good. The results of this research can also guide the authorities in Jati Cempaka Village to improve the quality of their website services to provide better benefits to the community and users.